Summarizing the 4D image stack of ultrafast dynamic contrast enhancement MRI of breast cancer in 3D using color intensity projections - Cover, Keith S.; Duvivier, Katya M.; de Graaf, Pim; Wittenberg, Rianne; Smit, Ruth; Kuijer, Joost P.A.; Hofman, Mark B.M.; Slotman, Ben J.; Verdaasdonk, Ruud M. (Journal of magnetic resonance imaging, 2019)
Background Each ultrafast dynamic contrast‐enhanced (DCE) MRI sequence for breast cancer generates thousands of images in a 4D stack that need to be reviewed by a radiologist. Purpose To assess whether color intensity projections (CIP) effectively summarizes—using only the time of arrival (ToA) and amount of signal enhancement (AoE) of the contrast agent—the thousands of ultrafast images. Study Type Retrospective cohort clinical trial. Subjects The study included 89 patients who had been scanned with an MRI beast protocol, of which 26 had breast cancer and 63 did not. Field Strength/Sequence The 115‐second ultrafast DCE sequence at 3T acquired 19 consecutive frames every 4.26 seconds with 152 slices per frame, yielding a 4D stack with 2888 2D images for each of water and fat. Assessment For each slice of the water 4D stack a single CIP image was generated that encoded the ToA in the hue (red, orange, yellow, green, cyan, blue) and AoE in the brightness. Each of three experienced radiologists assigned a Breast Imaging and Reporting Data System (BI‐RADS) score for each patient, first using only the CIP images, and subsequently using both CIP and the full 4D stack. Statistical Tests The one‐sided Fisher's exact test was used to determine statistical significance of both the sensitivity and specificity between the CIP alone and the CIP plus 4D stack. Results All malignancies were detected using only CIP by at least one of the radiologists. The CIP and CIP+4D sensitivities for reader 1 were 96% and 96% (P = 0.57), specificities were 59% and 65% (P = 0.29). For reader 2, the values were 96% and 100% (P = 0.51) with 62% and 71% (P = 0.17). For reader 3 the values were 92% and 96% (P = 0.50) with 51% and 62% (P = 0.07). Data Conclusion With a 95% sensitivity, CIP provides an effective summary of ultrafast DCE images of breast cancer. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1391–1399.